Achievement goals and self-determination in adult football players : a cluster analysis - Sarmento, Hugo (Array, 2018)
To better understand the relationship between aspects of motivation and performance level in adult football players, this study aimed to identify differences in motivation among different motivational profiles created by means of hierarchical cluster analysis. The participants were 304 adult football players (90 professionals, 144 semi-professionals, 70 amateurs, age: 25.4±4.6 years). Participants completed the Task and Ego Orientation in Sports Questionnaire and the Self-Regulation Questionnaire. Based on the constructs of the questionnaires, cluster analyses were performed. Chi-square was used to determine any relationships between the players and clusters. Four different clusters were identified. There was no typical motivational profile for football players of different competition levels. However, the differences in all four clusters represented specific characteristics of football players of different competition levels most represented in each respective cluster. Cluster 1, which was the most adaptive, was not related to any competition level. On the other hand, professional athletes were significantly less represented in the least adaptive motivational profile (Cluster 4). The results highlight the complex relationship between competition and sporting motivation. Identifying the motivational profile characteristics of football players who can reach higher competition levels presents itself as a future research opportunity.